Rhinopharyngitis and Low Back Pain on Drink Seller Housewife: Entrepreneurship Work at Home with the Lack of Help from Husband and Children - Kusumaningtyas, Intan (The Journal of The Indonesian Medical Students Association, 2010)
Introduction: The case study presents management of housewife whose sell a drink in her house which has rhinopharyngitis, low back pain and less attention from the family with holistic, comprehensive, integrated and continuous approach.Method: The data is collected from the primary data sources with anamnesis and physical examination.Result: There is a clinical improvement for the result. We also gave an intervention for the occupational problem and education for the family and community to make a healthy environment.Conclusion: We conclude that problem from this patient can not treat by using drugs only but also with changing lifting position and help from her family.ÃÂ Key words: rhinopharyngitis, low back pain, drink seller, housewife